1996
DOI: 10.1002/(sici)1097-0142(19960915)78:6<1272::aid-cncr16>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences between phosphotyrosine accumulation and Neu/ErbB-2 receptor expression in astrocytic proliferative processes: Implications for glial oncogenesis

Abstract: Upregulation of tyrosyl protein phosphorylation enables differentiation of neoplastic from nonneoplastic astrocytic proliferative states. Inhibition of this phosphorylation impairs growth of cells. Increased Neu receptor protein expression can distinguish malignant from low grade astrocytomas. We speculate that genetic events leading to stably increased phosphotyrosine may be critical for neoplastic transformation of astrocytes, whereas increased receptor tyrosine kinase expression could be a factor in the agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Of the cases studied (results from tumour biopsy), the range in results observed for HER2/neu in vivo positivity is wide (20 -90%). Some authors detect HER2/neu positivity without density analysis of receptors, so they report more than 70% positivity (Dietzmann and Von Bossanyi, 1994;Kristt and Yarden, 1996;Westphal et al, 1997;Bian et al, 2000). Some authors consider only the 2 þ and 3 þ tumours as positive, so they report only 20% positivity (Forseen et al, 2002;Koka et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the cases studied (results from tumour biopsy), the range in results observed for HER2/neu in vivo positivity is wide (20 -90%). Some authors detect HER2/neu positivity without density analysis of receptors, so they report more than 70% positivity (Dietzmann and Von Bossanyi, 1994;Kristt and Yarden, 1996;Westphal et al, 1997;Bian et al, 2000). Some authors consider only the 2 þ and 3 þ tumours as positive, so they report only 20% positivity (Forseen et al, 2002;Koka et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The HER2/neu (also called c-erbB2) receptor is not found in the adult central nervous system (Press et al, 1990), but it appears in tumoral astrocytes. Its expression increases with the degree of astrocytoma anaplasia (Kristt and Yarden, 1996) and becomes frequent in glioblastomas (20 -90%; Bian et al, 2000;Forseen et al, 2002;Koka et al, 2003). Overexpression of HER2/neu seems correlated to higher degree of glioma cells anaplasia (Kristt and Yarden, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2C, 3B,D). Double-staining studies of ErbB2 and GFAP clearly showed their colocalization on astrocytes, as in a previous observation with human biopsy samples (Kristt and Yarden, 1996). In addition, neuregulin was also detected on GFAP-positive cells (Fig.…”
Section: Expression Of Neuregulin Erbb2 and Erbb3 In Injured Brainsmentioning
confidence: 92%
“…As such, this aberrant EGFR does not bind any known EGFR ligand, but is a constitutively active tyrosine kinase which initiates mitosis independent of ligand-binding. The EGFRvIII has been detected in tumour cells only and is thought to play a significant role in the pathogenesis and aggressiveness of cancers (Kristt and Yarden, 1996;Moscatello et al, 1996;Nagane et al, 1996).…”
mentioning
confidence: 99%